How Knowledge Craft Safety Compliance Through Safety Culture in High-Risk Mining Company - Bella Carissa; Arum Etikariena; Wahyu Dwi Admaja (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: Addressing the prevention of occupational accidents is crucial, as the incidence of fatal workplace accidents in Indonesia remains alarmingly high, particularly within high-risk industries. The existing literature on the relationship between individual factors and knowledge of occupational safety is still limited. It is believed that safety knowledge in high-risk organizations can significantly reduce workplace accidents. This study aims to evaluate individual knowledge as an effective mechanism to mitigate occupational risks and accidents in high-risk companies in Indonesia. This research provides a fresh perspective on safety knowledge within high-risk industries, contrasting with the broader systems often depicted in previous literature. It also offers empirical evidence on how this knowledge can be effectively implemented at the individual level. Methods: The study was conducted a survey using questionnaire among 204 employees who works in high-risk mining industry in Indonesia. The collected was analyzed using Hayes PROCESS to analyze both direct and mediation relationships between safety knowledge, safety culture, and safety compliance. Results: The analysis revealed that safety culture serves as a mediator in the relationship between safety knowledge and safety compliance, confirming a direct relationship as well. Conclusion: The findings was confirmed the role of safety knowledge, mediated by safety culture, providing valuable insights and guidance for researchers and practitioners who aim to use individual knowledge as a tool for creating safer workplaces especially in high-risk organization.